Avaliação longitudinal da influência de três métodos de motivação indireta em higiene bucal em pacientes adultos - Nascimento, Ana Paula Camatta do (2009)
This study compares three motivational methods of oral hygiene in 78 adults students of the Training and Improvement Center of Military Policy of Espírito Santo (CFA). The patients were then divided into 4 randomized groups: group (I) for indirect motivation through a film, group (II) for indirect motivation through a folder, group (III) for indirect motivation through a lecture, and the control group (IV) with no motivational method for oral hygiene. All methods offer the same content for all groups, but for the patients in control group (IV), it was only presented at the end of the experiment. The patients were then assessed through the registration of individual indices of plaque and gingival at the beginning of the experiment, and then, 7, 30, 60, and 90 days after the motivational technique application. After assessing the patients in all four groups, statistical tests of variance analysis (ANOVA), Turkey’s test, and generalized linear models with repetition were performed on the data collected. The results of the average index of plaque at baseline and 7, 30, 60, and 90 days after the motivational method, are described respectively to Group (I), 1.04 (± 0.32), 0.49 (± 0.21), 0.65 (± 0.27), 0.58 (± 0.28) and 0.71 (± 0.30); Group (II): 1.09 (± 0.50), 0.65 (± 0.37), 0.76 (± 0.36), 0.75 (± 0.41) and 0.82 (± 0.36); Group (III): 1.09 (± 0.41), 0.74 (± 0.39), 0.73 (± 0,32), 0.60 (± 0.37) and 0.7 (± 0.23); Group (IV): 0.83 (± 0.41), 0.82 (± 0.33), 0.92 (± 0.40), 0.78 (± 0.27) and 0.81 (± 0.48). The results exhibit a significant reduction in plaque index seven days after the patients were subjected to the motivational method: -52.80% in group (I), -40.30% in group (II), and -32.1% in group (III). The control group (IV) remained stable across the experiment, and the result shows no statistically significant difference among the three experimental groups. For the average gingival index at baseline and 7, 30, 60, and 90 days, the results are: Group (I): 1.02 (± 0.52), 0.68 (± 0.40), 0.61 (± 0.36), 0.72 (±0.40) and 0.93 (± 0.42); Group (II): 1.24 (± 0.52), 0.67 (± 0.39), 0.92 (± 0.51), 0.85 (± 0.44) and 0.76 (± 0.53); Group (III): 1.34 (± 0.42), 0.77 (± 0.45), 0.49 (± 0,30), 0.80 (± 0.43) and 0.87 (± 0.41); Group (IV): 0.93 (± 0.59), 0.98 (± 0.41), 1.03 (± 0.51), 0.97 (±0.40) and 0.83 (± 0.48). The data for gingival index shows a significantly reduction seven days after the motivational technique application: -33.3% in group (I), -45.90% in group (II), and 42.5% in group (III). Stability in the control group (IV) and no statistically significant difference among the three experimental groups remained. In conclusion, all experimental groups managed to reduce the rates of plaque and gingival index seven days after the application of the motivational methods, however, there was no statistically significant difference among them. Despite the improvement of oral hygiene observed after the motivation period, there is an increase of the indices analyzed at the end of the experiment, but remained statistically lower than the baseline.